PENENTUAN UNIT COST PADA UMKM DI KABUPATEN GRESIK (Studi Kasus pada Masa Pandemi dan Program PPKM) - Safira Amelia Santoso; Rohmawati Kusumaningtias (Jurnal Bina Akuntansi, 2023)
The purpose of this study is to understand the determination of unit cost calculations on songkok painting products owned by Songkok Al Chambal MSMEs. The method used in this study is qualitative case study. The results showed that the calculation of Cost of Goods Produced according to the company and based on the full costing method obtained different results. Calculations according to the company include calculations that are not accurate, if you want to get the profit generated as expected. This can be seen from the difference in calculation of minus Rp 5,767. Getting minus results due to calculations using the full costing method resulted in a greater cost of Rp 31,302. Meanwhile, the company's calculation obtained a result of Rp 25,535. This difference is due to the calculation of its depreciation.